Social acceptance vital to success of novel food technologies - CHONG, Mark (Institutional Knowledge at Singapore Management University, 2023)
In a joint commentary, SMU Associate Professor of Communication Management (Practice) Mark Chong and Andrew Powell , CEO of Asia BioBusiness Pte Ltd, discussed how social acceptance is vital to the success of novel food technologies. They also explained how companies should be guided by the science of risk perception and behavioural science, and why a risk communication and engagement strategy is an essential component of risk management.